Archimedes assisted LSTM model for blockchain based privacy preserving IoT with smart cities - Somanathan Pillai, Sanjaikanth E Vadakkethil; Vallabhaneni, Rohith; Vaddadi, Srinivas A; Addula, Santosh Reddy; Ananthan, Bhuvanesh (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
Presently, the emergence of internet of things (IoT) has significantly improved the processing, analysis, and management of the substantial volume of big data generated by smart cities. Among the various applications of smart cities, notable ones include location-based services, urban design and transportation management. These applications, however, come with several challenges, including privacy concerns, mining complexities, visualization issues and data security. The integration of blockchain (BC) technology into IoT (BIoT) introduces a novel approach to secure smart cities. This work presents an Archimedes assisted long short-term memory (LSTM) model intrusion detection for BC based privacy preserving (PP) IoT with smart cities. After the stage of pre-processing, the LSTM is utilized for automated feature extraction and classification. At last, the Archimedes optimizer (AO) is utilized to optimize the LSTM’s hyper-parameters. In addition, the BC technology is utilized for securing the data transmission.